Pembuatan Katalog Produk, Profil dan Podcast Teaching Factory Rumah Kemasan A BEE sebagai Promotion Tools untuk Brand Awareness pada Fase Introduction dan Growth Stage - Yunelly Asra; Nur Anita; Hutomo Atman Maulana; Larbiel Hadi (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The purpose of this community service activity is to create promotional tools in the form of catalogs, profile videos and Teaching Factory of A BEE Packaging House, Department of Business Administration as an effort to build Brand Awareness because currently A Bee Packaging House is in the introduction phase towards the growth phase in the product life cycle. This activity is proposed in accordance with the department's request to introduce and grow demand for packaging design and printing services for products of business actors and MSMEs fostered by Polbeng. This activity is expected to increase brand awareness, capacity and productivity of A BEE Packaging House. The method used is to create catalog designs and prints, create profile videos uploaded on social media. The output of the activity is a product catalog, profile video, A BEE Packaging House and socialization of program results in seminars or media. The impact (outcome) of this activity is increased brand awareness of Rumah Kemasan A BEE in the eyes of business actors and MSMEs and increased demand for product packaging design and printing services for business actors and MSMEs fostered by Polbeng.